CYTOGENETICS OF REPRODUCTIVE DISORDERS IN MEN - Волков, Алексей Николаевич; Рытенкова, Оксана Ивановна; Лысенко, Денис Игоревич; Луговой, Константин Александрович (Medicine in Kuzbass, 2017)
Chromosomal abnormalities are a common cause of male infertility. Cytogenetic methods in combination with modern assisted reproductive technologies may, in some cases, significantly improve the reproductive status of men with impaired fertility, as well as reduce the risk of having children with an abnormal karyotype. Different types of chromosomal abnormalities associated with male infertility are considered, clinical manifestations and possible mechanisms of influence on reproductive function are discussed.